Cosmologies of selection: lessons from the faculty biscuit tin. Issue 12 (December 2016) - Bartlett, Maggie; Bartlett, Flora
Abstract: We conducted an ethnography of the faculty biscuit tin as we were interested in the lived experience of the biscuits contained within it. We used a constructivist epistemology, a social constructionist interpretive framework and a phenomenological methodology that included analysis from the perspectives of deixis and cosmology. The biscuits perceived that they were important to a selecting force and that the characteristics of one particular group had a specific value to the selector. Some enduring benefits may derive from the selection of this group, although its attractions were less immediately obvious than those of others. What is immediately attractive may not be the most fit for purpose; lessons for the selection of medical students may arise from this exploration of the selection experiences of biscuits in a faculty biscuit tin. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.